Independence and Caregiver Preferences Among Community-Dwelling Older People in Slovenia: A Cross-Sectional Study - Katarina Galof BSc OT, BOrgSc; Anja Žnidaršič PhD; Zvone Balantič PhD (SAGE Publishing, 2019)
Although Slovenia is becoming an aging society, very little is known about the abilities and needs of home-dwelling older people or their preferences regarding assistance. The aim of the study was to explore the need for assistance in daily activities among older Slovenian people living at home. Older adults aged between 65 and 97 years (N = 358) participated in the cross-sectional survey study. A questionnaire that assessed independence in daily activities and assistance in the home environment was developed. Data were analyzed using descriptive statistics, a nonparametric test (Wilcoxon signed rank test), and the chi-square test. The results showed that older Slovenians were more independent in activities of daily living (ADLs) than instrumental activities of daily living (IADLs). Independence was the highest for using the toilet, feeding, and mobility transfers, and the lowest for bathing. With IADLs, assistance was most often required with shopping and housework; this assistance was usually provided by family members. The provider of assistance was generally compatible with older people's preferences concerning assistance at home. We found no differences in care preferences between urban and rural settings. Assistance in the home environment was predominantly provided by unpaid helpers, which reflects recent developments in health and social services that put an emphasis on a person's social network. Due to demographic changes and the decrease in the number of adult children, reliance on close relatives might soon become a challenge. These findings can help policy makers understand older people's choices and preferences better when planning long-term care.